Parameters for Selection of Candidate Plus Trees of Terminalia Chebula and Terminalia Bellerica - Khobragade, N. D.; Prasad, Har; Surya Prabha, A. C.; Mandal, A. K. (Indian Forester, 2013)
This paper reports criteria for efficient selection of candidate plus tree/plus tree of Terminalia chebula and Terminalia bellerica for use in genetic improvement and conservation programme of the species.